Design and Implementation of an Archive Microservice solution for the Multi-AgentResearch and Simulation Distributed System - Prannoy Mulmi (Hochschule für angewandte Wissenschaften Hamburg, 2018)
This thesis introduces the design and implementation of an Archive Microservice in the Multi-Agent Research and Simulation (MARS) framework. Due to the distributed architecture of the system, the process of the archive and restore is complex to implement and maintain as there multiple possibilities of failure. This thesis uses different strategies to tackle the issues present in the system and provide an Archive service.